EXPRESSION OF ADHESION MOLECULES ON PERIPHERAL BLOOD MONOCYTES DURING PREGNANCY - V. A. Mikhaylova; Y. S. Klimovskaya; N. V. Amanova; M. S. Zaynulina; S. A. Selkov; D. I. Sokolov (Медицинская иммунология, 2014)
Peripheral blood monocytes play a key role in regulation of immune response during pregnancy. Intensive adhesion of monocytes to endothelium proves that monocytes are activated during pregnancy. To determine a potential role of adhesion molecules for ability of monocytes to adhere, we studied expression of CD11a, CD11b, CD11c, CD18, CD49d, CD29 markers of monocytes from non-pregnant and pregnant women. Expression of adhesion molecules on monocytes was analyzed by flow cytometry. The amounts of CD11b-expressing monocytes increased during pregnancy, as compared with non-pregnant women. Intensity of CD11a, CD11b, CD11c, CD29 expression on the monocytes did also increase at normal pregnancy. These results suggest that intense adhesion of monocytes to endothelium during uncomplicated pregnancy may be determined by increased expression of CD11a, CD11b, CD11c, CD29, and higher amounts of CD11b+ monocytes.